Trade and sustainable finance for development - Gianni Vaggi (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Sustainable development is a long-term process, and as such must be examined carefully. Development implies structural changes of many different types, ranging from purely economic aspects to those affecting the personal circumstances of people. Changes take time, all the more so when dealing with structural change in the economic composition of output/exports, as well as in the habits and norms that regulate consumption and saving patterns. Thus, we are dealing with a long-term process, in which the evolution of the process itself and initial conditions are of extreme importance. Here lies one of the advantages of tackling development from the point of view of a historian of economic persuasion. There may also be disadvantages, but one certainly learns how to keep a close watch on three issues: the need to consider longterm time horizon; the role of initial conditions, and the implications of structural change, both in economic and social terms. Any consideration of the long-term sustainability of external finance for developing countries must be evaluated within these simple but often ignored perspectives. The twenty-year old debt crisis is also a story about common sense facts, which at times have been either ignored or even isolated. Lessons have been learned, but with great difficulty. Nevertheless, the recent 1996 Heavily Indebted Poor Countries Initiative and the subsequent debates have brought to the fore some of this forgotten evidence. This should be used in efforts to outline a framework for finance for development which might be sustainable by debtor countries, thus preventing future crises. – debt ; sustainability ; trade
Keywords: F34; F36; O19; 330; Nachhaltige Entwicklung; Internationaler Kredit; Außenwirtschaft; Entwicklungsländer